2015
DOI: 10.3923/ijss.2015.130.141
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Penetration Resistance and Soil Moisture Distribution in a Sandy Loam Soil (Eutric leptosol)

Abstract: Bivariate relations between penetration resistance and soil moisture content was conducted on sandy loam soil (Eutric leptosol) at the University of Juba demonstration farm. Soil Penetration Resistance (PR) was measured using an Eijkelkamp pocket penetrometer to a depth of 0-15 cm depth with Soil Moisture Content (SMC) measured using an Eijkelkamp sensor theta probe. Measured SMC within the plots varied from 9-35% whereas, the PR varied from 0.1 to 4.5 kg cmG 2 . The results showed significant negative correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(15 reference statements)
0
4
1
1
Order By: Relevance
“…However, these findings are contrary to the previous studies reported by several researches (e.g. Veronese et al, 2006;Van Quang et al, 2012;Lomeling and Möri Lasu, 2015) that show that penetration resistance is negatively correlated to soil moisture content. In this study, positive correlation between soil penetration resistance and moisture content can be attributed to the change in bulk density and macro pores caused by soil planking, prevention of the loss of soil moisture content and the capillary rise of water from subsoil to topsoil.…”
Section: Correlations Between Soil Properties and Root Growth Parameters Evaluatedcontrasting
confidence: 99%
“…However, these findings are contrary to the previous studies reported by several researches (e.g. Veronese et al, 2006;Van Quang et al, 2012;Lomeling and Möri Lasu, 2015) that show that penetration resistance is negatively correlated to soil moisture content. In this study, positive correlation between soil penetration resistance and moisture content can be attributed to the change in bulk density and macro pores caused by soil planking, prevention of the loss of soil moisture content and the capillary rise of water from subsoil to topsoil.…”
Section: Correlations Between Soil Properties and Root Growth Parameters Evaluatedcontrasting
confidence: 99%
“…Soil water reduces contact between particles, reducing penetration resistance (Lomeling & Lasu, 2015). However, this was not observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The layers that presented higher relative density and penetration resistance contained higher clay content (data not shown) and an amount of cryptopores, which resulted in more compacted soil. Considering that from 2 MPa, the root growth may be restricted (Lomeling & Lasu, 2015; Taylor, Roberson, & Parker, 1966), subsoiled and non‐subsoiled soil presented adverse physical conditions for root growth in 11–60 cm layer.…”
Section: Discussionmentioning
confidence: 99%
“…Able to characterize spatial patterns soil compaction [68] Soil diagnostic and geographic information systems (GIS)…”
Section: Rapideye Remote Sensingmentioning
confidence: 99%
“…Made proportional sampling more accurate [71] Kriging and inverse distance weighting interpolation have been tested in SSA [68] and have been found to be able to characterize spatial patterns soil compaction that is useful information for site-specific soil management practices in precision agriculture. Spatial variability provided by kriged contour maps of individual soil nutrients together with cone index is useful in decision making to ensure appropriate management practices that are specific to crop fields [53].…”
Section: Reducing Variability Within a Farm Management Zonementioning
confidence: 99%